2009
DOI: 10.1002/tax.583009
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships in the Spermacoceae alliance (Rubiaceae) using information from six molecular loci: insights into systematic affinities of Neohymenopogon and Mouretia

Abstract: Several recent phylogenetic studies of Rubiaceae have dealt with enigmatic taxa whose systematic positions have been previously unknown or controversial. We address evolutionary relationships in the Spermacoceae alliance (Rubioideae) with special emphasis on the Asian genera Mouretia and Neohymenopogon, here sequenced for the first time. Both genera belong in the tribe Argostemmateae and have persistent calyx lobes on the fruit in common with Argostemma and Mycetia. Other previous uncertainties are resolved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 70 publications
7
62
5
Order By: Relevance
“…4). The results also elucidated that the tribes Spermacoceae and Knoxieae, which were classified as a subclade of the Spermacoceae alliance by Rydin et al (2009b), grouped into an isolated clade too. Danaideae separated from other clades with very strong support values, as revealed by Rydin et al (2009b).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…4). The results also elucidated that the tribes Spermacoceae and Knoxieae, which were classified as a subclade of the Spermacoceae alliance by Rydin et al (2009b), grouped into an isolated clade too. Danaideae separated from other clades with very strong support values, as revealed by Rydin et al (2009b).…”
Section: Discussionmentioning
confidence: 84%
“…Our extensive sampling from the all available taxa in the Spermacoceae alliance and preliminary phylogenetic analyses on the basis of single or combined loci indicated that the new genus was nested within the subclade that included the tribes Anthospermeae, Argostemmateae, Dunnieae, Paederieae, Putorieae, Rubieae, and Theligoneae (Rydin et al, 2009b). Further phylogenetic analysis based on four combined chloroplast sequences revealed that Foonchewia was sister to Dunnieae, which included the monotypic genus Dunnia Tutch., with high support value (88% bootstrap value and 100% Bayesian posterior probability, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The c. 21 tribes of the Rubioideae fall into a basal grade and two major groups: the Psychotrieae alliance (sensu Razafimandimbison et al 2008, Rydin et al 2009a = supertribe Psychotriidinae sensu Robbrecht & Manen 2006; see also fig. 1) and the Spermacoceae alliance (sensu Rydin et al 2009b = supertribe Rubiidinae sensu Robbrecht & Manen 2006; see also fig. 1).…”
Section: Rubioideae and The Spermacoceae Alliancementioning
confidence: 99%